DNA barcoding of commonly prevalent Culicoides midges in South India - M, ARCHANA; D SOUZA, PLACID E; JALALI, S K; RENUKAPRASAD, C; OJHA, RAKSHITH (The Indian Journal of Animal Sciences, 2015)
DNA barcoding has gained increased recognition as a molecular tool for species identification of insects. Interspecific variation in DNA sequences of some genes is much higher than intraspecific and provides an opportunity to use DNA sequences for species identification. A study was therefore undertaken to barcode 5 commonly prevalent CuliCOIdes species in farming regions of Bengaluru districts in Karnataka state. The barcoding of Cytochrome oxidase I (COI) gene of C. anophelis, C. palpifer, C. huffi, C. innoxius and C. circumscriptus yielded an amplified fragment of 648 bp sequence. Barcode for all 5 species was generated using BoldSystems v3 and submitted to genbank for accession numbers. DNA barcoding enabled exact identification of 5 prevalent species.